O28 Neoliberal policy reforms & biomedical residualism in community mental health practice in england. (20th March 2019) - Moth, Rich
Abstract : Background: Mental health policy initiatives in England over the last three decades have led to significant restructuring of statutory service provision. One feature of this has been the reconfiguration of NHS mental health services to align with the requirements of internal and external markets in the context of wider neoliberal organisational transformations. Aims/Objectives: This paper examines the effects of neoliberal policy and service reforms on professional practice and conceptualisations of mental distress within one mainstay of NHS statutory services: the community mental health team (CMHT). Methods: The paper is based on findings from twelve months' ethnographic fieldwork and semi-structured interviews with practitioners and service users within two CMHTs. Results and conclusions: The paper begins with an account of the restructuring of the labour process in mental health services. This utilises the notion of 'strenuous welfarism' 1 to describe an organisational context characterised by escalating performance management, deskilling of professional practice and the intensification of mental health work. The study found that increasingly prominent aspects of managerialism and marketization disrupted attempts by mental health practitioners to sustain supportive and mutual structures with colleagues and engage with service users in therapeutic and relationship-based forms of practice. Moreover organisational processes increasingly recast service users as individual consumers 'responsibilised' to manage their own risk, or subject to increasingly coercive measures when perceived to have failed to do so. Consequently biomedical orientations were remobilised in practice in spite of a rhetorical shift in policy discourse towards socially inclusive approaches. The term 'biomedical residualism' is coined to describe this phenomenon. However instances of ethical professionalism that reflected resistance to these residualised modes of practice were also visible. Reference: Mooney G and Law A. New Labour/hard labour?: restructuring and resistance inside the welfare industry . Policy Press, 2007.